2018
DOI: 10.3390/fluids3020040
|View full text |Cite
|
Sign up to set email alerts
|

Material Transport under a Wave Train in Interaction with Constant Wind: A Eulerian RANS Approach Combined with a Lagrangian Particle Dispersion Model

Abstract: The interaction of a developed train of gravity deep water waves with suddenly applied winds is investigated in this manuscript. The direction of the wind is the same as that of the wave train (i.e., following) and its imposed surface shear stress is constant and steady. The focus of this study is on a micro-scale water wave field where the time scale is on the order of ten wave periods and the length scale is on the order of ten wave lengths. Accurate 2D Reynolds-averaged Navier-Stokes (RANS) multi-phase simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…While Cherukat et al documented separation of flow at a/λ = 0.05, Yoon et al [11], in their DNS study at the same Reynolds number as Cherukat et al [9] observed small recirculation at the trough of the solid wave for a/λ = 0.02 and a distinct reversal of flow at a/λ = 0.03. Turbulent flow over wavy surfaces is extensively studied in the context of air flow over water waves [12][13][14][15][16][17]. Notable among them is the DNS investigation in a three-dimensional (3D) domain presented by Sullivan et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…While Cherukat et al documented separation of flow at a/λ = 0.05, Yoon et al [11], in their DNS study at the same Reynolds number as Cherukat et al [9] observed small recirculation at the trough of the solid wave for a/λ = 0.02 and a distinct reversal of flow at a/λ = 0.03. Turbulent flow over wavy surfaces is extensively studied in the context of air flow over water waves [12][13][14][15][16][17]. Notable among them is the DNS investigation in a three-dimensional (3D) domain presented by Sullivan et al [12].…”
Section: Introductionmentioning
confidence: 99%